1991
DOI: 10.1002/cne.903100106
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of galanin‐like immunoreactivity in the brain of Rana esculenta and Xenopus laevis

Abstract: The immunocytochemical distribution of galanin-containing perikarya and nerve terminals in the brain of Rana esculenta and Xenopus laevis was determined with antisera directed toward either porcine or rat galanin. The pattern of galanin-like immunoreactivity appeared to be identical with antisera directed toward either target antigen. The distribution of galanin-like immunoreactivity was similar in Rana esculenta and Xenopus laevis except for the absence of a distinct laminar distribution of immunoreactivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…The location of orexogenic peptides in the anuran brain is also similar to that in the mammalian brain. Galanin-like (Lázá r et al, 1991;Olivereau and Olivereau, 1992), neuropeptide-Y-like (Danger et al, 1985;Lázár et al, 1993), and orexin-like (Galas et al, 2001) immunoreactive cells and fibers were located in the preoptic area, the magnocellular preoptic nucleus, and the ventral hypothalamus. Cells showing melanin concentrating hormonelike immunoreactivity in the frog brain were restricted to the posterior tubercle, periventricular organ, and the dorsal hypothalamic nucleus .…”
Section: Possible Functional Role Of Cart Peptides In Brain Areas Relmentioning
confidence: 94%
See 1 more Smart Citation
“…The location of orexogenic peptides in the anuran brain is also similar to that in the mammalian brain. Galanin-like (Lázá r et al, 1991;Olivereau and Olivereau, 1992), neuropeptide-Y-like (Danger et al, 1985;Lázár et al, 1993), and orexin-like (Galas et al, 2001) immunoreactive cells and fibers were located in the preoptic area, the magnocellular preoptic nucleus, and the ventral hypothalamus. Cells showing melanin concentrating hormonelike immunoreactivity in the frog brain were restricted to the posterior tubercle, periventricular organ, and the dorsal hypothalamic nucleus .…”
Section: Possible Functional Role Of Cart Peptides In Brain Areas Relmentioning
confidence: 94%
“…The nomenclature used to designate nuclei and pathways in the frog brain was mostly according to Lázá r et al (1991), whereas some structures in the telencephalon were named according to Marín et al (1998).…”
Section: Digital Imagingmentioning
confidence: 99%
“…All these hypothalamic nuclei contain neuroendocrine neurons that project to the median eminence and the neurointermediate lobe of the pituitary (Neary and Northcutt 1983;Tuinhof et al, 1994). In frog, some of these neurons express various hypophysiotropic neuropeptides such as corticotropin-releasing factor , thyrotropin-releasing hormone (Lamacz et al, 1989), somatostatin (Laquerrière et al, 1989), growth hormonereleasing hormone (Marivoët et al, 1988), gonadotropinreleasing hormone (Andersen et al, 1988;Collin et al, 1995), pituitary adenylate cyclase-activating polypeptide (Yon et al, 1992), ␣-melanocyte-stimulating hormone (Benyamina et al, 1986), melanin-concentrating hormone (Andersen et al, 1986), neuropeptide Y (Danger et al, 1985), enkephalins (Merchenthaler et al, 1989), calcitonin gene-related peptide (Mulatero and Fasolo, 1991), and galanin (Lázá r et al, 1991). That hcrt-immunoreactive fibers were not detected in the frog median eminence suggests that hcrts do not directly regulate the activity of adenohypophysial cells.…”
Section: Comparative Distribution Of Hcrt-related Peptides In the Cnsmentioning
confidence: 98%
“…The distribution of these peptides was described only in the tectum in the literature covered by this review. We found earlier (Lázá r et al, 1991;Merchenthaler et al, 1989) that ENK-and GAL-ir nerve fibers showed a characteristic complementary arrangement in the npB and Cg. Since the other peptides discussed in this review are poorly represented in the LGC, I illustrate enkephalin and GAL immunoreactivity in photomicrographs from my collection.…”
Section: Lateral Geniculate Complexmentioning
confidence: 79%
“…In R. esculenta, a loose network of thick ir-fibers was found in lamina G and the inner half of layer 8. Dot-like fiber particles occurred in lamina B and D, while in layers 6 to 3 loosely arranged ir-fibers could be stained (Lázá r et al, 1991) (Figs. 2E, 5B,D, 6).…”
Section: Corticotropin Releasing Factor (Crf) (Table 1mentioning
confidence: 98%